Aplikasi Sistem Informasi Bursa Kerja Khusus (BKK) Bagi Alumni Universitas Papua Dengan Metode Rapid Application Development (RAD) Menggunakan Framework Codeigniter: Application Of The Special Job Exchange Information System (BKK) For University Of Papua Alumni With Rapid Application Development (RAD) Method Using The Codeigniter Framework - Herlina Barrang; Christian Dwi Suhendra; Lorna Yertas Baisa (Universitas Papua, 2024)
This research was conducted to create an Information System that can make it easier for alumni to find jobs according to their competence. The goal is that alumni can access job vacancy information that matches their interests and expertise through the platform provided by this application. Job search can be adjusted according to certain criteria, and the system provides automatic notifications for suitable vacancies. In addition, Special Job Exchange (BKK) managers can track alumni activities, add job vacancies, and track alumni placements using this application. The speed, scalability, and performance that the CodeIgniter framework offers are advantages. Using the Rapid Application Development (RAD) development method, the system can be developed with client orientation. The test results show that this application can help alumni find jobs. This will benefit both parties.